Measuring The Contribution of Investment, Export and Internet Usage on Welfare: Indonesian Case Study - Ira Febriana Sari (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
This study aims to investigate the influence of investment, exports, and the internet usage on people's welfare, as measured by Regional GDP (RGDP) per capita and the Human Development Index (HDI). The estimation technique employed is Fixed Effect Model with path analysis approach applied to 34 provinces in Indonesia for the period of 2016-2020. The finding suggests that local government spending, exports, and internet use have a positive and significant effect on the RGDP per capita of which act as intervening variable, thus those three variables are indirectly affect HDI. Furthermore, RGDP per capita, local government spending, and investment are simultaneously have a positive and significant effect on HDI. However, according to t-statistic result, the impact of FDI is not significant statistically. This is possibly due to the FDI schemes in Indonesia of which constitute as non-project investment, where technology spillover is considered minimum, and capital gains tend to be savored by its beneficial owner in foreign countries.